Dampak Media Sosial dan Pengaruhnya Dalam Perubahan Sosial-Budaya Berpakaian Masyarakat Suku Nias - Lestari Loi (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Information and Communication Technology (ICT) brings change and development to society. ICT, which ultimately gave birth to social media, causes people's behavior and life patterns to experience a shift in existing culture, ethics and norms. Indonesia, which consists of millions of people and various racial, religious, ethnic and diverse cultures, has great potential opportunities for social change. Social media has a big influence and impact on a culture, both positive and negative. Especially for the Nias ethnic community, social media has influenced almost all existing aspects and fields. One of them is the culture and customs of the Nias tribe which have been influenced by social media. In this era of rapid progress, everyone can follow a style and lifestyle according to something that is considered trendy. This research uses a descriptive method - literature review using a phenomenological approach and reliable reference sources. On this occasion, the author tries to examine socio-cultural changes resulting from the impact and influence of social media on the Nias ethnic community.